2022
DOI: 10.1186/s12909-022-03348-0
|View full text |Cite
|
Sign up to set email alerts
|

Crossword puzzle as a learning tool to enhance learning about anticoagulant therapeutics

Abstract: Background Educational games make the learning process more enjoyable, fun, and create a competitive classroom environment that can positively affect learning. The purpose of this study was to evaluate pharmacy students’ perceptions of crossword puzzles (CWPs) as a learning tool in the pharmacotherapy cardiovascular module focusing on anticoagulants’ therapeutics and assessing if students’ preference of learning style influenced their perception. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…In the present study there was no significant relationship between gender and perception towards METAPAD gaming puzzle. While there was a significant difference reported among males and females in the study that used the same survey instrument by Ghada Bawazeer et al [ 14 ], towards the question that assessed the perceptions on the length of time provided for solving puzzles. Male students did not show much satisfaction towards the time allocated to solve the puzzle in their study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study there was no significant relationship between gender and perception towards METAPAD gaming puzzle. While there was a significant difference reported among males and females in the study that used the same survey instrument by Ghada Bawazeer et al [ 14 ], towards the question that assessed the perceptions on the length of time provided for solving puzzles. Male students did not show much satisfaction towards the time allocated to solve the puzzle in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The same study evaluating the association between different learning styles and perceptions of crossword puzzles in pharmacology reported no significant difference among the two [ 14 ]. In contrast, the current study’s results highlight the importance of considering the match between learning styles and instructional approaches when incorporating innovative educational tools like the METAPAD gaming puzzle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the sole strategy of online education did not result in an increase in MBSS result documentation compliance, rather the chart review showed a decrease in compliance. Some researchers suggest that PowerPoint presentations can oversimplify a complex process leading these authors to believe the EHR screen logic of the MBSS process may have been too difficult to replicate in a single-learning modality without opportunities for interaction between learner and trainer 24. Despite 100% return of the crossword puzzle in the first PDSA cycle, demonstrating its ability to engage staff,18 the overall results showed a modest increase for the MBSS result documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest that PowerPoint presentations can oversimplify a complex process leading these authors to believe the EHR screen logic of the MBSS process may have been too difficult to replicate in a single-learning modality without opportunities for interaction between learner and trainer. 24 Despite 100% return of the crossword puzzle in the first PDSA cycle, demonstrating its ability to engage staff, 18 the overall results showed a modest increase for the MBSS result documentation. However, the risk factor documentation did increase, which could possibly be the result of this strategy being effective for recalling information and not application of that information as needed in the branching logic seen in the EHR screening form.…”
Section: Discussionmentioning
confidence: 99%